The genetic diversity of heat shock protein 70 gene at promoter and 5' untranslated region in beef cattle - Suhendro, I.; Jakaria, J.; Noor, R.R. (Journal of the Indonesian Tropical Animal Agriculture, 2021)
This study was aimed to identify genetic diversity in the promoter area and 5' UTR (untranslated region) HSP70 (heat shock protein 70) gene in several beef cattle in Indonesia. A total of 86 blood samples of Bali, Madura, PO (Peranakan Ongole), Limousine, and BB (Belgian Blue) cattle were used in this study. The extracted DNA of all blood samples was then analyzed using the direct sequencing method. The genotyping results showed the presence of five SNP (Single Nucleotide Polymorphism) in the promoter region, namely g.-393T>C, g.-343C>A, g.-202T>C and g.-69T>G and three SNPs at 5' UTR, i.e., g.19A>G, g.45C>T, and g.100_101ins30. The frequency of SNP alleles found in PO, Limousine, and BB cattle was in equilibrium, whereas in Bali and Madura cattle populations, the allele frequency was disequilibrium. In general, the level of diversity of observed alleles ranged from low to high (0.26-1.00), where SNP g.19A>G had the widest variety. It was successfully revealed in this analysis that the SNP g.-69T>G binds to both the NF-Y and CAAT box transcription factor. In addition, the 30 bp (base pair) insertions (g.100_101ins30) that were identified in Bali and Madura cattle have never been reported in previous research studies.